Postpartum hemorrhage and prolonged hyperfibrinolysis as complications of uterine cavernous hemangioma: a case report and literature review - Xue-Li Bai; Xia Cao (Clinical and Experimental Obstetrics & Gynecology)
Background: Uterinecavernous hemangioma can cause persistent vaginal bleeding or massive hemorrhage and can lead to severe pregnancy complications. Case: A 23-year old woman with cutaneous hemangiomas presented for caesarean delivery of her second child nine days after successful delivery, she was admitted with severe postpartum hemorrhage and disseminated intravascular coagulation (DIC). A hysterectomy was performed as a result. The diagnosis of cavernous uterine hemangioma was made only on histopathological examination. In addition, an atypically extended period of refractory fibrinolytic hyperactivity developed after hysterectomy. Such extensive hyperfibrinolysis has not previously been reported in conjunction with hysterectomy. Conclusion: This case underscores the importance of cavernous uterine hemangioma as one of the causes of refractory uterine bleeding at the time of operation delivery. The definitive diagnosis can be made only on histological examination. Changes in the coagulation mechanism should be monitored closely during postpartum, and clinicians should be aware of the possibility of fibrinolytic hyperactivity.